Role of LINC00152 in non-small cell lung cancer - Yu, Hong (Zhejiang University Press, 2020)

(untitled) (J Zhejiang Univ Sci B)
Non-small cell lung cancer (NSCLC) accounts for about 85% of all lung cancer cases. The pathogenesis of NSCLC involves complex gene networks that include different types of non-coding RNAs, such as long non-coding RNAs (lncRNAs). The role of lncRNAs in NSCLC is gaining an increasing interest as their function is being explored in various human cancers. Recently, a new oncogenic lncRNA, LINC00152 (cytoskeleton regulator RNA (CYTOR)), has been identified in different tumor types. In NSCLC, the high expression of LINC00152 in tumor tissue and peripheral blood samples has been shown to be associated with worse prognoses of NSCLC patients. Overexpression of LINC00152 has been confirmed to promote the proliferation, invasion, and migration of NSCLC cells in vitro, as well as increase tumor growth in vivo. This review discusses the role of LINC00152 in NSCLC.